Targeting the epigenetic regulation of ferroptosis: a potential therapeutic approach for sepsis-associated acute kidney injury - Yuhang Yang; Xinqi Deng; Wenyuan Li; Yan Leng; Yonghong Xiong; Bihan Wang; Siyuan Gong; Yunhao Wang; Baichuan Yang; Wei Li (Clinical Epigenetics)
Abstract Sepsis is a syndrome of organ dysfunction caused by the invasion of pathogenic microorganisms. In clinical practice, patients with sepsis are prone to concurrent acute kidney injury, which has high morbidity and mortality rates. Thus, understanding the pathogenesis of sepsis-associated acute kidney injury is of significant clinical importance. Ferroptosis is an iron-dependent programmed cell death pathway, which is proved to play a critical role in the process of sepsis-associated acute kidney injury through various mechanisms. Epigenetic regulation modulates the content and function of nucleic acids and proteins within cells through various modifications. Its impact on ferroptosis has garnered increasing attention; however, the role of epigenetic regulation targeting ferroptosis in sepsis-associated acute kidney injury has not been fully elucidated. Growing evidence suggests that epigenetic regulation can modulate ferroptosis through complex pathway networks, thereby affecting the development and prognosis of sepsis-associated acute kidney injury. This paper summarizes the impact of ferroptosis on sepsis-associated acute kidney injury and the regulatory mechanisms of epigenetic regulation on ferroptosis, providing new insights for the targeted therapy of sepsis-associated acute kidney injury.